Efficiency performance of China's health care delivery system. (7th June 2017) - Zhang, Luyu; Cheng, Gang; Song, Suhang; Yuan, Beibei; Zhu, Weiming; He, Li; Ma, Xiaochen; Meng, Qingyue
Summary: Improving efficiency performance of the health care delivery system has been on the agenda for the health system reform that China initiated in 2009. This study examines the changes in efficiency performance and determinants of efficiency after the reform to provide evidence to assess the progress of the reform from the perspective of efficiency. Descriptive analysis, Data Envelopment Analysis, the Malmquist Index, and multilevel regressions are used with data from multiple sources, including the World Bank, the China Health Statistical Yearbook, and routine reports. The results indicate that over the last decade, health outcomes compared with health investment were relatively higher in China than in most other countries worldwide, and the trend was stable. The overall efficiency and total factor productivity increased after the reform, indicating that the reform was likely to have had a positive impact on the efficiency performance of the health care delivery system. However, the health care delivery structure showed low system efficiency, mainly attributed to the weakened primary health care system. Strengthening the primary health care system is central to enhancing the future performance of China's health care delivery system.